Chronic Diseases and Labor Market Outcomes in Egypt - Rocco, Lorenzo; Tanabe, Kimie; Suhrcke, Marc; Fumagalli, Elena (2012)
By causing a sizeable reduction in employment 6 percent and labor supply 19 percent, chronic diseases are responsible for a major efficiency loss in the Egyptian economy. Furthermore the impact of chronic diseases on the labor market is not uniformly distributed. The older and the less educated suffer a larger drop in the probability of being employed and in their supply of working hours. The authors estimate the reduced form equations of individual employment status, labor supply and the usual wage equation. They control for unobserved ability and individual preferences by means of a within-siblings estimator. Measurement errors in our self-reported health variable have been accounted for.